Effect of dietary probiotics as antibiotic alternative on growth performance, organ development and meat quality in broiler chicken - Sarker, Md Sazedul Karim; Rana, Md Masud; Sultana, Shabiha; Hossain, Noor; Sarker, Nathu Ram; Nahar, Talukder Nurun (Asian Journal of Medical and Biological Research, 2017)
The aim of the study was to evaluate the effect of dietary probiotics on broiler growth performance, organ development and meat quality in replacing oxytetracycline. Dietary treatments were control (basal diet without additives), antibiotic (basal diet with 0.05% oxytetracycline), basal diet with Bacillus subtilis and basal diet with Lactobacillus spp. A total of 192 birds were randomly allotted to four dietary treatments with four replicates having 12 birds each. Feed and water were supplied ad libitum. The results of the current study revealed that growth performances of broiler did not show significant difference (P>0.05) among the treatments. Body weight and weight gain were numerically higher and FCR was numerically lower in broilers fed a diet containing 2 different single strains of probiotic than control. Though there were no treatment effects (P>0.05) on the weights of the liver, heart, kidney, spleen, gizzard, intestine and dressing percentage, but abdominal fat content was found significantly higher (P<0.05) in antibiotic treated group than that of single strain probiotic (Lactobacillus spp.) feeding group. Significant differences were also observed in meat color values where antibiotic fed broiler meat showed higher redness, lower lightness and yellowness and birds fed the control feed had higher lightness and yellowness of meat than probiotic fed chicken. TBA, PH and cooking loss were not affected by the treatments. Therefore, we concluded that use of selected probiotics resulted in improved performance parameters and reduced abdominal fat pad in broiler chickens. Moreover, addition of the probiotics in broiler diet for replacing antibiotic could be utilized for safe poultry meat production. Asian J. Med. Biol. Res. June 2017, 3(2): 233-239